Farmers’ Knowledge Gaps in Irrigation Modernization: A SECI Model Approach in the Krueng Aceh Region - Dewi Sri Jayanti; Ferijal Teuku (The University of Lampung, 2026)
The modernization of irrigation systems requires farmers to manage knowledge effectively, adapt to technological changes, and participate actively in increasingly complex institutional arrangements. This study analyzed farmers’ knowledge gaps (K-Gap) and the knowledge transformation process using the SECI model in the Krueng Aceh region. A descriptive mixed-methods approach was applied through interviews, observations, questionnaires, and documentation. Quantitative analysis using PLS-SEM assessed inter-variable relationships, while K-Gap and IPA identified priority knowledge areas. All constructs met validity and reliability requirements, with Composite Reliability values ranging from 0.835 to 0.982 and AVE values between 0.559 and 0.933. The conformity level of 99.32% indicated strong alignment between farmers’ perceptions and expectations of institutional performance. K-Gap analysis showed that infrastructure had the highest knowledge gap (0.05), while water management had the lowest (0.02). The integrated results of IPA and SECI revealed strengths in the socialization and internalization stages, indicated by active participation, mutual cooperation, and consistent water distribution, while weaknesses were concentrated in the externalization and combination stages, particularly in documentation and knowledge integration. Therefore, strengthening SECI-based knowledge management is recommended, with emphasis on improved documentation, technical capacity building, and more effective support systems to ensure the sustainability of irrigation modernization in the Krueng Aceh.